2016
DOI: 10.1038/ncomms13018
|View full text |Cite
|
Sign up to set email alerts
|

EIN2-dependent regulation of acetylation of histone H3K14 and non-canonical histone H3K23 in ethylene signalling

Abstract: Ethylene gas is essential for many developmental processes and stress responses in plants. EIN2 plays a key role in ethylene signalling but its function remains enigmatic. Here, we show that ethylene specifically elevates acetylation of histone H3K14 and the non-canonical acetylation of H3K23 in etiolated seedlings. The up-regulation of these two histone marks positively correlates with ethylene-regulated transcription activation, and the elevation requires EIN2. Both EIN2 and EIN3 interact with a SANT domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
150
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 127 publications
(161 citation statements)
references
References 64 publications
5
150
0
Order By: Relevance
“…1B). To confirm the Western blot result at the molecular level, we revisited previously published ChIP-seq data of H3K14Ac and H3K23Ac from Col-0 and ein2-5 mutant plants (23). In the ein2-5 mutant, levels of both H3K14Ac and H3K23Ac were lower than in Col-0 plants, whereas no significant difference was detected for H3K9Ac ( Fig.…”
Section: Ein2mentioning
confidence: 99%
See 4 more Smart Citations
“…1B). To confirm the Western blot result at the molecular level, we revisited previously published ChIP-seq data of H3K14Ac and H3K23Ac from Col-0 and ein2-5 mutant plants (23). In the ein2-5 mutant, levels of both H3K14Ac and H3K23Ac were lower than in Col-0 plants, whereas no significant difference was detected for H3K9Ac ( Fig.…”
Section: Ein2mentioning
confidence: 99%
“…Previous work demonstrated that EIN2 is involved in the regulation of H3K14Ac and H3K23Ac levels in ethylene response (23). To explore the molecular mechanisms that underlie this regulation, we examined the levels of H3K14Ac and H3K23Ac in EIN2 S645A transgenic plants, in which EIN2-C is constitutively localized to the nucleus, and these plants display a constitutive ethylene responsive phenotype (18).…”
Section: Ein2mentioning
confidence: 99%
See 3 more Smart Citations